Baghbhairab Temple: An Exploration of Historical and Modern Development - Maharjan, Babita (Shahid Kirti Multidisciplinary Journal, 2025)
The Baghbhairab Temple is located in Kirtipur, Nepal which is a significant religious and historical site dedicated to Baghbhairab. The Hindu god Bhairab is represented as a tiger. Baghbhairab Temple is known for its cultural and architectural importance. It is a major hub for regional celebrations and worship, especially the yearly Baghbhairab Jatra. So, in this study, I explore the historical narratives of Baghbhairab temple. This research design is qualitative and involves systematic collection of information by interviewing interview guidelines. The present events are field-based methods that observe the human emotions, opinions, feelings and their cultural practices. It also explores religious activities, socio-cultural practices and cultural representations of the past reality and present changes in a different way. The Baghbhairab Temple stands as evidence to the rich cultural heritage and religious devotion of the Newar community in Kirtipur, stand for centuries-old traditions and craftsmanship. The findings of this study show that, there are many historical narratives of Baghbhairab temple but the most popular one is related to children and goats. The name of the Baghabhairab is the identification of the people of Kirtipur which is widely use this name in different organization because people have strong belief of God Baghbhairab. It has its unique narrations and architectural structure and myth of origin of Baghbhairab. There are some small monuments in the periphery of the temple which have their own values. Local people with Baghbhairab Guthi and local government play vital roles to conserve heritage sites.